2015
DOI: 10.3109/00365513.2014.984320
|View full text |Cite
|
Sign up to set email alerts
|

Adair-based hemoglobin equilibrium with oxygen, carbon dioxide and hydrogen ion activity

Abstract: As has been known for over a century, oxygen binding onto hemoglobin is influenced by the activity of hydrogen ions (H⁺), as well as the concentration of carbon dioxide (CO₂). As is also known, the binding of both CO₂and H⁺ on terminal valine-1 residues is competitive. One-parametric situations of these hemoglobin equilibria at specific levels of H⁺, O₂or CO₂are also well described. However, we think interpolating or extrapolating this knowledge into an 'empirical' function of three independent variables has n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
7
0
2
Order By: Relevance
“…3). A new model recently published by Mateják et al (2015), while this article was under preparation, also fits some of these experimental data well under altered physiological conditions. Their approach, a modification of Adair’s four-step algorithm (Adair, 1925), considers the problems in depth, and, like ours, relates the O 2 -Hb and CO 2 -Hb binding effects to the acid-base chemistry of blood based on pH and P CO2 , as proposed by Siggaard-Andersen and others over the years (Rossi-Bernardi & Roughton, 1967; Forster et al , 1968; Siggaard-Andersen, 1971; Siggaard-Andersen & Salling, 1971; Bauer & Schroder, 1972; Siggaard-Andersen et al , 1972a; Siggaard-Andersen et al , 1972b; Siggaard-Andersen & Garby, 1973; Siggaard-Andersen et al , 1984; Siggaard-Andersen & Siggaard-Andersen, 1990).…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations
“…3). A new model recently published by Mateják et al (2015), while this article was under preparation, also fits some of these experimental data well under altered physiological conditions. Their approach, a modification of Adair’s four-step algorithm (Adair, 1925), considers the problems in depth, and, like ours, relates the O 2 -Hb and CO 2 -Hb binding effects to the acid-base chemistry of blood based on pH and P CO2 , as proposed by Siggaard-Andersen and others over the years (Rossi-Bernardi & Roughton, 1967; Forster et al , 1968; Siggaard-Andersen, 1971; Siggaard-Andersen & Salling, 1971; Bauer & Schroder, 1972; Siggaard-Andersen et al , 1972a; Siggaard-Andersen et al , 1972b; Siggaard-Andersen & Garby, 1973; Siggaard-Andersen et al , 1984; Siggaard-Andersen & Siggaard-Andersen, 1990).…”
Section: Resultsmentioning
confidence: 56%
“…The recent model of Mateják et al (2015), based on their version of the Adair equation (1925), is reported to fit well, the data of Severinghaus and colleagues (Roughton et al , 1972; Roughton & Severinghaus, 1973; Severinghaus, 1979), and is also shown to fit the temperature and pH-dependent S HbO2 data of Reeves (1980) and Naeraa (1963), and carbaminohemoglobin data of Bauer and Schröder (1972) and Matthew (1977). Our present S HbO2 and S HbCO2 models fit these diverse data sets as accurately, and also fit the P CO2 , pH, and temperature-dependent data of Joels and Pugh (1958) and Hlastala et al (1977), which were not used by Mateják et al (18).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…These factors influence P 50 either directly or indirectly through each other. Many groups have studied these factors to create models capturing each parameter's influence on P 50 40,41,43‐46 . These groups have assessed the effect of these parameters as well as their synergistic effects using experimental data and computational methods in order to model transport and exchange of oxygen in the lungs and tissue 47 .…”
Section: Oxyhemoglobin Dissociation Modelmentioning
confidence: 99%